2013
DOI: 10.1037/a0032336
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of working memory processes to relational matching-to-sample performance in baboons (Papio papio).

Abstract: Recent studies of monkeys and apes have shown that these animals can solve relational-matching-to-sample (RMTS) problems, suggesting basic abilities for analogical reasoning. However, doubts remain as to the actual cognitive strategies adopted by nonhuman primates in this task. Here, we used dual-task paradigms to test 10 baboons in the RMTS problem under three conditions of memory load. Our three test conditions allowed different predictions, depending on the strategy (i.e., flat memorization of the percept, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…We stress that we do not believe that animals, especially Old-World primates, are qualitatively lacking in their capacity to process relations or even to match relations. They continue to reveal intriguing glimmers of relational cognition Flemming, Thompson, & Fagot, 2013;Martinho & Kacelnik, 2016;Maugard, Marzouki, & Fagot, 2013;Pepperberg, 2013;Vonk, 2003). These findings make the problem of relational cognition's evolutionary emergence far more interesting.…”
Section: Discussionmentioning
confidence: 94%
“…We stress that we do not believe that animals, especially Old-World primates, are qualitatively lacking in their capacity to process relations or even to match relations. They continue to reveal intriguing glimmers of relational cognition Flemming, Thompson, & Fagot, 2013;Martinho & Kacelnik, 2016;Maugard, Marzouki, & Fagot, 2013;Pepperberg, 2013;Vonk, 2003). These findings make the problem of relational cognition's evolutionary emergence far more interesting.…”
Section: Discussionmentioning
confidence: 94%
“…We also note that, although the majority of studies identified in our review, unsurprisingly, tested aspects of primate social cognition (e.g., social learning, cooperation, competition, and communication), this was not exclusively so. Highlighting that a social test setting does not prohibit the testing of non-social cognition, our review revealed tests of, for example, analogical reasoning ( Fagot & Maugard, 2013 ), memory ( Fagot & de Lillo, 2011 ; Maugard, Marzouki & Fagot, 2013 ), visual perception ( Cheries et al, 2006 ), numerical understanding ( Hauser, Carey & Hauser, 2000 ), and personality ( Carter et al, 2012 ; Neumann et al, 2013 ), although we note the inherent complexity of teasing apart “social” from “non-social” cognition (c.f. Seyfarth & Cheney, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maugard, Marzouki, and Fagot, (2013) used dual-task procedures to test baboons familiar with the RMTS task (Fagot & Thompson, 2011) under three conditions of memory load that permitted Maugard et al (2013) to predict the specific strategy employed by their animals (i.e., flat memorization of the percept, recoding of the percept, or relational processing). Their results were consistent with the prediction that the baboons processed both the items and the abstract (same and different) relations in this task.…”
Section: Discussionmentioning
confidence: 99%
“…Their results were consistent with the prediction that the baboons processed both the items and the abstract (same and different) relations in this task. Whether or not Maugard et al (2013) results can be demonstrated by either rhesus or capuchin monkeys currently remains unanswered.…”
Section: Discussionmentioning
confidence: 99%